The rhetoric of antisemitism : from the origins of Christianity and Islam to the present - Kiewe, Amos (Lexington Books, 2021)
"The Rhetoric of Antisemitism explores the roots of antisemitism that are based in the religious tension between Judaism and Christianity from antiquity and onward. The primary argument is that the religious foundations of Christianity, and later in Islam, were advanced by depressing Judaism and that negative attitudes toward Judaism became generic"--